Pengaruh Variasi Rasio Prekursor terhadap Kristalinitas Nanopartikel ZnO Hasil Sintesis Hijau Berbasis Ekstrak Parthenium hysterophorus L. - Nahzim Rahmat; Prisca Caesa Moneteringtyas; Pina Budiarti Pratiwi; Trisno Afandi (JURNAL REDOKS : JURNAL PENDIDIKAN KIMIA DAN ILMU KIMIA, 2026)
This study aims to synthesize ZnO nanoparticles via a green synthesis approach using Parthenium hysterophorus L. leaf extract with two variations of precursor ratios. The process was carried out at a temperature range of 65–85 °C followed by calcination at 600 °C for 2 hours. FTIR analysis showed a strong absorption band at 840 cm⁻¹ corresponding to Zn–O stretching vibrations, along with several organic functional groups (C–O, C=O, C=C) acting as natural stabilizing agents. XRD patterns confirmed the formation of the wurtzite ZnO phase without impurities, with crystallite sizes calculated by the Scherrer equation of 0.87 nm (Sample A) and 0.94 nm (Sample B). The sharper peaks observed in Sample B indicate higher crystallinity. These findings demonstrate the effectiveness of P. hysterophorus L. extract as a natural bioreductant in the eco-friendly synthesis of ZnO nanoparticles